PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IV SD NEGERI 015 TALANG JERINJING KECAMATAN RENGAT BARAT - Rapida Rapida; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: This research aims to improving the result of science Learning of fourth grade students at SDN 015 Talang Jerinjing academic year 2014 / 2015. Subject of the research are fourth grade students at SDN 015 Talang Jerinjing as many as 20 students. the from of This research is collaborative class research action with two cycles, while the problem is low of science learning result caused by less varied of learning. the data of This research show that result of students learning have increased, the result value of teacher activity on first cycles with an average 68.52%. on second cycles have increased with an average 85,93s%. student activity on first cycles with an average 64.06% . on second cycles have increased with an average 89.06% .Result of the data have increasing where in before taking action cooperative learning model Jigsaw type on basis score who is complated are 8 person (40%) with an average 60,05. first cycles increased who is completed get up 13 persen (65%) with an average 68,08. On scond cycles have increased who is completed get up to 17 persen (85%) with an average 76,02%. The en han cement of totality learning result is 26,59%. There fore it can conclude that hypothesis in this research is